The novel 5-HT1A receptor agonist, NLX-112 reduces l-DOPA-induced abnormal involuntary movements in rat: A chronic administration study with microdialysis measurements. (June 2016) - McCreary, Andrew C.; Varney, Mark A.; Newman-Tancredi, Adrian
Abstract: Althoughl -DOPA alleviates the motor symptoms of Parkinson's disease (PD), it elicits troublesomel -DOPA-induced dyskinesia (LID) in a majority of PD patients after prolonged treatment. This is likely due to conversion ofl -DOPA to dopamine as a ' false neurotransmitter ' from serotoninergic neurons. The highly selective and efficacious 5-HT1A receptor agonist, NLX-112 (befiradol or F13640) shows potent activity in a rat model of LID (suppression of Abnormal Involuntary Movements, AIMs) but its anti-AIMs effects have not previously been investigated following repeated administration. Acute administration of NLX-112 (0.04 and 0.16 mg/kg i.p.) reversedl -DOPA (6 mg/kg)-induced AIMs in hemiparkinsonian rats with established dyskinesia. The activity of NLX-112 was maintained following repeated daily i.p. administration over 14 days and was accompanied by pronounced decrease of striatal 5-HT extracellular levels, as measured by in vivo microdialysis, indicative of the inhibition of serotonergic activity. A concurrent blunting ofl -DOPA-induced surge in dopamine levels on the lesioned side of the brain was observed upon NLX-112 administration and these neurochemical responses were also seen after 14 days of treatment. NLX-112 also suppressed the expression of AIMs in rats that were being primed for dyskinesia by repeatedl -DOPA administration. However, when treatment of these rats with NLX-112 was stopped, l -DOPA then induced AIMs with scores that resembled those of control rats. The present study shows that the potent anti-AIMs activity of NLX-112 is maintained upon repeated administration and supports the ongoing clinical development of NLX-112 as a novel antidyskinetic agent for PD patients receivingl -DOPA treatment. Highlights: NLX-112 is a selective 5-HT1A receptor agonist which eliminates L-DOPA-induced Abnormal Involuntary Movements in Parkinsonian rats. The potent anti-AIMs activity of NLX-112 (0.16 mg/kg i.p.) is maintained over a once-daily 2-week dosing period. NLX-112 did not prevent the 'priming' process that causes rats to express AIMs in response to repeated dosing of L-DOPA. NLX-112 maintained a robust inhibition of striatal serotonin release and blunting of L-DOPA-induced increases in dopamine levels. NLX-112 did not modify striatal glutamate release but reversed L-DOPA-induced increases in striatal GABA release.